Globalization and Growth in the Australian Manufacturing Sector: A Comparison of the Performance of the Subdivisions - Andrew Marks (Contemporary Research in Business, Management and Economics Vol. 6, 2024)
Aims: The fundamental objective of the study is to assess the relative growth performance of the subdivisions of the Australian manufacturing sector in a globalized environment as reflected in trade liberalization in the period 1968/69-2021/22. Study Design: The study involves primary data which is used to formulate figures and tables. Place and Duration of Study: University of Western Sydney, School of Business between December 2022 and January 2024. Methodology: Figures and tables are used as the main framework of the analysis of the study. Results: The capital-intensive manufacturing subdivisions have exhibited a stronger growth performance relative to the more labor-intensive manufacturing subdivisions. For example, the former category is characterized by coal, petroleum and related products manufacturing and metal product manufacturing growing by 3.6 and 2,6 percent respectively compared to textile, clothing and footwear manufacturing which is representative of the latter category growing by 0.1 of one percent in the period 1968/69 -2021/22. Conclusion: Manpower policies are required to re-train the unemployed labor emanating from the contraction of the labor-intensive manufacturing subdivisions to enhance employment prospects in the expanding capital-intensive manufacturing subdivisions.